2023
DOI: 10.1371/journal.pone.0284110
|View full text |Cite
|
Sign up to set email alerts
|

Many-objective African vulture optimization algorithm: A novel approach for many-objective problems

Abstract: Several optimization problems can be abstracted into many-objective optimization problems (MaOPs). The key to solving MaOPs is designing an effective algorithm to balance the exploration and exploitation issues. This paper proposes a novel many-objective African vulture optimization algorithm (MaAVOA) that simulating the African vultures’ foraging and navigation behaviours to solve the MaOPs. MaAVOA is an updated version of the African Vulture Optimization Algorithm (AVOA), which was recently proposed to solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Key features of AVOA encompass modeling hunger as solution quality, physical strength as exploration radius, adaptive flight through adjustable parameters, and conflict avoidance via separation distance. We have considered the AVOA as our main candidate algorithm for this study, aiming to maximize visual comfort metrics, for the following reasons: Recent development: AVOA, introduced in 2021 29 , is a newly developed algorithm undergoing active refinement 30 35 , offering opportunities for further improvement and application expansion. Documented efficiency: Preliminary studies have demonstrated AVOA's consistently impressive performance, often surpassing established metaheuristic algorithms on benchmark optimization tasks 29 , 35 37 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Key features of AVOA encompass modeling hunger as solution quality, physical strength as exploration radius, adaptive flight through adjustable parameters, and conflict avoidance via separation distance. We have considered the AVOA as our main candidate algorithm for this study, aiming to maximize visual comfort metrics, for the following reasons: Recent development: AVOA, introduced in 2021 29 , is a newly developed algorithm undergoing active refinement 30 35 , offering opportunities for further improvement and application expansion. Documented efficiency: Preliminary studies have demonstrated AVOA's consistently impressive performance, often surpassing established metaheuristic algorithms on benchmark optimization tasks 29 , 35 37 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent development: AVOA, introduced in 2021 29 , is a newly developed algorithm undergoing active refinement 30 35 , offering opportunities for further improvement and application expansion.…”
Section: Literature Reviewmentioning
confidence: 99%